Investigation on the use of red and yellow light-emitting diodes (LEDs) to promote growth, proximate composition and cell morphology of marine microalga Tetraselmis sp. - Kamarul Zaman, Nuur Fatin (2016)
The growth and proximate composition of marine microalga, Tetraselmis sp.using red and yellow color LEDs and fluorescent as a control were compared under different wavelengths. There were no significant differences (p > 0.05) between the red, yellow and fluorescent lights during the 11 days of culture except fluorescent light had higher cell density and optical density compared to red on day 12 & 13. However,specific growth rates showed similar values. Lipid and protein content was significantly higher under red LEDs whereas, carbohydrate composition show significant higher under floursescent light. In terms of cell morphology observe under scanning electron microscope (SEM), the sizes of the cells among the treatments did not reveal significant difference. The cells were broad elliptical in initial stage and elliptical in final stagein in all three lights. There were also dividing cells and flagella observed on the cells. Final stage shows the cell is more folded especially under the yellow LED and significant difference between initial and final in term of size. The results showed that Tetraselmis sp. had similar growth rate, and and cell morphology under the red, yellow LEDs and fluorescent light wherease high carbohydrate in florescent light and high protein and lipid under red LED.